2022
DOI: 10.1093/geronb/gbac020
|View full text |Cite
|
Sign up to set email alerts
|

Self-Enhanced False Memory Across the Life Span

Abstract: Objectives The role of self in veridical memory has been extensively studied, but what is the role of self in false memory development across the life span? The current study examined the impact of self-reference on associative false memory in children, younger adults, and older adults, and further investigated possible mechanisms concerning how self-reference might impact false memory in different age groups. Method Combinin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Subsequent research also revealed that self‐reference facilitated the false binding between the lure items and the self (i.e., participants formed more self‐lure associative memories; Wang, Otgaar, Howe, & Cheng, 2021). Using the DRM paradigm, this enhancing effect of the self on the production of spontaneous false memories of words has been consistently found in various age groups, including children, younger adults, and older adults (Ozdes et al., 2021; Rosa & Gutchess, 2013; Wang et al., 2022).…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Subsequent research also revealed that self‐reference facilitated the false binding between the lure items and the self (i.e., participants formed more self‐lure associative memories; Wang, Otgaar, Howe, & Cheng, 2021). Using the DRM paradigm, this enhancing effect of the self on the production of spontaneous false memories of words has been consistently found in various age groups, including children, younger adults, and older adults (Ozdes et al., 2021; Rosa & Gutchess, 2013; Wang et al., 2022).…”
Section: Introductionmentioning
confidence: 88%
“…Of special interest here, eyewitnesses can be either victims of a crime who experience the crime from a self‐referential perspective and thus process information in relation to themselves or can be bystanders who witness the crime happening to others. The self is a complex set of active goals and associated self‐images (Conway, 2005), and presenting cues such as one's own name or own image could serve as an operation to activate the self (Cunningham et al., 2014; Wang et al., 2018, 2022). Encoding information in relation to oneself (e.g., one's own name or image) is well‐known for its effect on shaping memory (Klein, 2012; Symons & Johnson, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon has been termed as the self-reference effect (SRE). The SRE has been demonstrated for diverse materials including words, pictures, lms, birthdays and names (Bredart, 2016; Burden Most studies on the SRE on false memory used the semantic DRM paradigm (e.g., Wang et al, 2019;Wang et al, 2022), in which lists of semantically related stimuli (e.g., bed, dream, rest, pillow) are presented in the study phase and a semantically related unpresented critical lure (e.g., sleep) is presented in the test phase. Subjects usually claim that the critical lure was presented in the study phase.…”
Section: Introductionmentioning
confidence: 99%
“…Subjects usually claim that the critical lure was presented in the study phase. The augment effect of self-referential processing on false memory has been found for various materials including words, events (Bays & Foley, 2015), for young and old ages (Lee et al, 2016;Pitarque et al, 2017;Wang et al, 2022;Rosa & Gutchess, 2013), and for subjects of western and eastern cultures (Wang et al, 2019). Relational processing and elaborative processing account have been proposed to explain the SRE on true memory (Straube, 2012; Lee et al, 2016;Bays & Foley, 2015;Zhang et al, 2020;Toglia, 1999;Bower & Gilligan, 1979;Pitarque et al, 2017).…”
Section: Introductionmentioning
confidence: 99%